2010
DOI: 10.1007/s11295-010-0327-5
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and mapping multiple S-locus F-box genes in European pear (Pyrus communis L.)

Abstract: European pear, as well as its close relatives Japanese pear and apple, exhibits S-RNase-based gametophytic self-incompatibility. The male determinant of this self-incompatibility mechanism is a pollen-expressed protein containing an F-box domain; in the genera Petunia (Solanaceae), Antirrhinum (Plantaginaceae), and Prunus (Rosaceae), a single F-box gene determines the pollen S. In apple and Japanese pear, however, multiple S-locus F-box genes were recently identified as candidates for the pollen S, and they we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 57 publications
4
19
0
Order By: Relevance
“…Map-based cloning and chromosome walking approaches to study the Solanaceae, Plantaginaceae, and Rosaceae S loci have commonly identified multiple pollen-expressed F-box genes flanking the S-RNase gene (Fig. 3;de Franceschi et al, 2011;Entani et al, 2003;Lai et al, 2002;Minamikawa et al, 2010;Okada et al, 2008Okada et al, , 2010Okada et al, , 2013Sassa et al, 2007;Ushijima et al, 2001Ushijima et al, , 2004Wang et al, 2003Wang et al, , 2004Wheeler and Newbigin, 2007;Zhou et al, 2003). Compared with that of the genus Prunus, the recombination-suppressed region around the S locus is much larger and more highly heterochromatic in the tribe Maleae and the families Solanaceae and Plantaginaceae, making it difficult to isolate the true pollen S gene in these three plant taxa (Entani et al, 1999a;Yang et al, 2007).…”
Section: Identification Of F-box Genes As the Pollen S Gene Candidatementioning
confidence: 99%
“…Map-based cloning and chromosome walking approaches to study the Solanaceae, Plantaginaceae, and Rosaceae S loci have commonly identified multiple pollen-expressed F-box genes flanking the S-RNase gene (Fig. 3;de Franceschi et al, 2011;Entani et al, 2003;Lai et al, 2002;Minamikawa et al, 2010;Okada et al, 2008Okada et al, , 2010Okada et al, , 2013Sassa et al, 2007;Ushijima et al, 2001Ushijima et al, , 2004Wang et al, 2003Wang et al, , 2004Wheeler and Newbigin, 2007;Zhou et al, 2003). Compared with that of the genus Prunus, the recombination-suppressed region around the S locus is much larger and more highly heterochromatic in the tribe Maleae and the families Solanaceae and Plantaginaceae, making it difficult to isolate the true pollen S gene in these three plant taxa (Entani et al, 1999a;Yang et al, 2007).…”
Section: Identification Of F-box Genes As the Pollen S Gene Candidatementioning
confidence: 99%
“…In an accompanying paper, we have characterized SFBB homologs in the European pear (Pyrus communis L.) and have analyzed their genetic linkage to the S-RNase (De Franceschi et al 2010). The results presented in that paper suggested that the actual number of SFBB-related genes present at the S-locus region of the European pear is higher than the number of genes initially reported for the S-locus of the apple and the Japanese pear (P. pyrifolia Nakai) .…”
Section: Communicated By a Abbottmentioning
confidence: 99%
“…Although the Prunus pollen S was originally referred to by two different terms, SFB and SLF (Entani et al, 2003), we use SFB in this article because it distinguishes the Prunus system from other systems, and recent studies have all used SFB (Newbigin et al, 2008;Sassa et al, 2010;Tao and Iezzoni, 2010). The S locus F-box brothers (SFBBs) have been identified as candidates for the pollen S determinant in the subtribe Pyrinae of the Rosaceae (De Franceschi et al, 2011a, 2011bKakui et al, 2011;Minamikawa et al, 2010;Okada et al, 2008Okada et al, , 2011Sassa et al, 2007). Variants of the S locus defined by combinations of molecular mechanism of GSI, possibly because unidentified pollen and/or pistil factors play important roles in the SI/SC reaction.…”
Section: Introductionmentioning
confidence: 99%